The monuments men : allied heroes, Nazi thieves, and the greatest treasure hunt in history - Edsel, Robert M. (Center Street, 2009)
"The previously untold story of a little-known WWII Allied division whose mission was to track down European art and treasures that had been looted by the Nazis at Hitler's command"--Provided by the publisher